Laparoscopic versus open distal pancreatectomy - Šlepavičius, Algirdas; Nutautienė, Vitalija (Lietuvos chirurgija, 2015)
Objective The aim of the study is to estimate effectiveness of surgical approaches: laparoscopic (LDP) and conventional distal pancreatectomy (TDP) for benign and non-invasive lesions in the body and tail of pancreas . Materials and methods Comparative retrospective study of demographic, pathotological, operative data, which were taken from the medical records of all patients undergoing LDP and TDP between 1998–2015 in the Klaipeda University hospital. Until 1998 all patients were operated on by conventional approach. From 2006 all patients were operated by laparoscopic approach. Results We conducted 62 distal pancreatectomies: 30 of LDP and 32 of TPD. Both of these comparative groups (TPD and LDP) were not different according to the demographical and pathohistological data, but it was different according operative and postoperative indicators. Quantity of blood loss was higher in the TPD group (p – 0.012). There were more cases of spleen preservation in TPD group, but the difference was not significant. Fistulas of pancreas in TPD (11) and LDP (7) groups were not significant different (p – 0.31). There was significantly higher need for analgesic (ketonal, morphine) after the operation in TPD group (p – 0.03, p – 0.01). After LDP patients spend less time in hospital (p – 0.01). Death cases after operations in both groups were not recorded. Conclusion Both operations of LDP and TPD are safe while removing diseases of distal pancreas. Study showed that complications in LDP and TPD were similar, postoperative fistula frequency of pancreas was similar. In comparison of results, LDP has these advantages: less blood loss, less time in hospital, less need of analgesics, faster return to active life. It is great need of prospective randomized study in the future to compare both methods.
Keywords: distal pancreatectomy; laparoscopy; pancreatic neoplasms